Sophocles and the Greek language : aspects of diction, syntax and pragmatics - Jong, Irene J. F. de.; Rijksbaron, Albert. (Mnemosyne, Supplements, 2006)
This volume offers an extensive overview of the various ways in which Sophocles' use of the Greek language is currently being studied. Greatly admired in antiquity, Sophocles' style only became a serious subject of investigation with Campbell's Introductory essay On the language of Sophocles (1879). Fourteen chapters, divided into three sections (diction, syntax, pragmatics), discuss the linguistic register and use of gnomai in Ajax' deception speech, Homeric intertextuality, the style of the Sophoclean satyr-plays in relation to tragedy and comedy, the relation between the repetition of words and focalization, the language of blindness, the image of 'fire', the use of deictic pronouns, the semantics of the middle-passive and of counterfactuals, the historic present and the constitution of the text, the suggestive power of descriptions, speech-acts, and strategies of politeness.